Danshensu protects vascular endothelia in a rat model of hyperhomocysteinemia - Yang, Rui-xue (Nature Publishing Group, 2010)
AIM: To examine whether danshensu could protect vascular endothelia in a rat model of hyperhomocysteinemia. METHODS: The model was established by feeding rats with a methionine-rich diet (1 g·kg(−1)·d(−1)) for 3 months. Immediately following the discontinuation of methionine-rich diet, rats were treated with danshensu (67.5 mg·kg(−1)·d(−1), po) or saline for 3 additional months. One group of rats receiving vitamin mixture (folic acid, vitamin B12 and vitamin B6) was included as a positive control. One group of rats not exposed to methionine-rich diet was also included as a blank control. The expression of tumor necrosis factor-alpha (TNF-alpha) and intercellular adhesion molecule-1 (ICAM-1) protein in the descending aorta was examined using immunohistochemistry and Western blot. Homocysteine and blood concentration of endothelin and nitric oxide (NO) was also examined. RESULTS: Methionine-rich diet resulted in accumulation of “foam cells”, up-regulated expression of TNF-alpha and ICAM-1 in the descending aorta, and significantly increased serum homocysteine. Plasma endothelin concentration was significantly increased; NO was decreased. Danshensu treatment, either simultaneous to methionine-rich diet or afterwards, attenuated the above mentioned changes. CONCLUSION: Chronic treatment with danshensu could prevent/attenuate the formation of atherosclerosis. Potential mechanisms include inhibited expression of representative proinflammatory cytokines and adhesion molecules in arterial endothelia. Changes in homocysteine and circulating molecules that control vascular contraction/relaxation via endothelial cells (eg, endothelin and NO) were also implicated.